Identification, Growth Study, Encapsulation And Characterization Of Potential Prebiotic And Probiotic Extracted From Selected Fruit Peels - Akter, Beauty (2024)
This study focused on waste utilization for an economical and alternative natural source of potential prebiotic and probiotic production. Moreover, prebiotic-based biopolymeric encapsulation was also conducted to develop synbiotic powder for improved survival of Lactobacillus plantarum CAM 4 under gastrointestinal and storage conditions. Phase 1 of the study aimed to assess the prebiotic potential of watermelon rind/peel, pineapple, and banana peels by analysing their impact on the growth rate of probiotics.